The Production of Tetraploid Swainsona formosa by Colchicine Mutagenesis - , Zulkarnain (Zuriat, 2004)
Swainsona formosa, a legume native to Australia, is a spectacular flowering plant that is used as a hanging basket, container or cut flower plant. Its breeding programme had been emphasized on the production of better flower quality through ploidy modification to produce tetraploid plants. Colchicine, an antimitotic chemical, had been sucessfully used to induce tetraploidyzation in S. formosa. Up to 50% of plants with double chromosome number (2n = 4x = 32) were produced by seedling application of colchicine at 0.01%–0.1%. Concentrations below 0.01% or above 0.1% were found not effective in inducing chromosome doubling. Tetraploid S. formosa were charaterized by larger leaflets, bigger size but lower density of stomata, larger flowers with longer peduncles and larger pollen grains with lower viability. In general, colchicine can be used effectively to induce polyploidyzation in S. formosa and this method should find application in breeding programme.